Fulfillment of the Rights and Obligations of Husbands and Wives with Disabilities from the Perspective of the Bahsul Masail NU Regency Institution Pemalang : Case study in North Wanarejan Village, Pemalang Regency - Sofiatun Nufusul Karimah (Asian Journal of Law and Humanity, 2023)
Rights are things that a person receives from other people, while the obligations referred to here are what a person should do to other people. The rights and obligations in this family aim to make each member aware of their obligations to others. One of the obligations that must be carried out is family maintenance. It is someone’s expenditure in the form of a need for someone who is obliged to provide for it. Fulfillment of these rights and obligations must be fulfilled by every married couple, including persons with disabilities. In fact, in the aspect of family and marriage, persons with disabilities have difficulties in carrying out household life. They cannot fully fulfill their rights and obligations as husband and wife for reasons of their disability. Even though persons with disabilities who are married cannot be separated from their obligations as husband and wife. They still have to fulfill their obligations as befits a husband and wife. This research takes the perspective of the Bahsul Masal Institute of PCNU Pemalang Regency, where the Bahsul Masail Institute is a forum for discussion of scholars to discuss problems in society, especially Nahdiyyin residents who make up the majority in North Wanarejan Village.